2021
DOI: 10.3390/jcm11010044
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Bronchitis—A Serious Rare Complication Affecting Children Only after Fontan Procedure?

Abstract: Background: Plastic bronchitis (PB) may occur not only in children following palliative Fontan procedure but also in those without underlying heart disease. We aim to assess the clinical course, therapeutic measures, outcome, and follow-up of PB in children with congenital heart disease (CHD) and children without cardiac problems. Methods: This retrospective case series assessed children with PB admitted to hospital between 2015 and 2019. Parents or guardians of patients were contacted by e-mail or telephone b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…The present study found that the pathology of PB with right ventricular dysfunction showed a small number of neutrophils and fibrin infiltration, which was consistent with the pathology of type 2 PB [7]. Studies have shown that the occurrence and development of type 2 PB are related to abnormal lymphatic circulation (10)(11). Children after Fontan or Glenn surgery may be due to the high flow of pulmonary blood vessels or increased pulmonary vascular resistance, which leads to the increase of intrapulmonary vascular exudation and the aggravation of a load of intrapulmonary lymphatic circulation (12)(13).…”
Section: Discussionsupporting
confidence: 88%
“…The present study found that the pathology of PB with right ventricular dysfunction showed a small number of neutrophils and fibrin infiltration, which was consistent with the pathology of type 2 PB [7]. Studies have shown that the occurrence and development of type 2 PB are related to abnormal lymphatic circulation (10)(11). Children after Fontan or Glenn surgery may be due to the high flow of pulmonary blood vessels or increased pulmonary vascular resistance, which leads to the increase of intrapulmonary vascular exudation and the aggravation of a load of intrapulmonary lymphatic circulation (12)(13).…”
Section: Discussionsupporting
confidence: 88%
“…They reported that patients with CHD usually developed bronchial casts on the right side, and patients without CHD usually developed bronchial casts on the left side. 14 Lung function tests play an important role in evaluating respiratory diseases such as asthma; however, lung function data reported from patients with PB are limited. 11 A recent study showed that three patients with mild airflow obstruction had normal lung function tests during follow-up and had stopped ICS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients in our study were diagnosed as having nonstructural heart disease, and they had similar cast localizations with cast development on the left side. Pałyga‐Bysiecka et al 14 compared the characteristics of children with CHD and children without CHD among patients with PB. They reported that patients with CHD usually developed bronchial casts on the right side, and patients without CHD usually developed bronchial casts on the left side 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the occurrence and development of type 2 PB are related to abnormal lymphatic circulation (10)(11). Children after Fontan or Glenn surgery may be due to the high ow of pulmonary blood vessels or increased pulmonary vascular resistance, which leads to the increase of intrapulmonary vascular exudation and the aggravation of a load of intrapulmonary lymphatic circulation (12)(13).…”
Section: Discussionmentioning
confidence: 99%